John But and the ending of the a version of Piers Plowman - Horobin, S (Brepols Publishers, 2020)
This article reconsiders the conclusion to the A version of Piers Plowman attributed to John But. Where previous critics have sought to identify the historical John But on the assumption that this will shed light on the biography of William Langland, the article adopts a more sceptical stance. Instead of viewing John But as a member of Langland’s coterie, the article suggests that John But’s knowledge of the author may have been entirely derived from reading, and perhaps copying, his work.